Effect of limited-creep feeding calves of spring-calving cows grazing native grass - Brazle, F.; Kuhl, Gerry L.; Corah, L.; Zoellner, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two limited-creep feeding trials were conducted with spring-born, suckling calves on native grass. The high-energy creep rations containing an ionophore were fed during the last 63 or 85 days before weaning in the two trials. Creep intake was limited with salt to about 1.5 lb per calf daily. Calves consuming the limited-creep feeds gained .26 to .31 lb more per head daily and required 4.4 to 5.5 lb of creep per lb of extra weaning weight.
Keywords: Beef; Creep feeding; Calves; Cows; Grass